The Optimization Feeding Rate Towards Saline Tilapia Production in Stagnant Waters, Pekalongan City - Fahrurrozi, Ashari; Madusari, Benny Diah; Syakirin, Mohammad Bahrus; Linayati, Linayati; Mardiana, Tri Yusufi; Wijianto, Heri Ariadi; Budianto, Budianto (Department of Aquaculture, 2024)
The flood disaster in the coastal area of Pekalongan City resulted in stagnant water, thus impacting the livelihoods of the community previously. The adaptation that has been made to deal with these conditions is by cultivating saline tilapia. Feed is the most important factor in supporting the growth of saline tilapia production. However, research on feed quality and frequency that has been carried out for tilapia production has not been optimal in obtaining the results obtained. This study aims to determine the effect of different feeding rates on growth performance, feed utilization and survival rate of tilapia reared in stagnant brackish water. The study consisted of feeding rates of 3%, 5%, 7% and 9% with three replications, and parameters were observed every seven days. Based on the research results it is known that the optimal feeding rate in saline tilapia culture ranges from 6.67% - 7% based on growth parameters. Although the other parameters do not show the same feeding rate as the growth parameter, these parameters are still in a good range for saline tilapia culture.